2019
DOI: 10.32615/bp.2019.009
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of proline and non-protein thiols in response to low temperature and cadmium stresses in wheat

Abstract: This is an open access article distributed under the terms of the Creative Commons BY-NC-ND Licence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Moreover, in our study the higher GSH concentrations in the winter conditions can be attributed also to higher Cd tissue concentrations observed in this season, since GSH synthesis is strongly Cd‐induced (Seth et al 2012). Also, Repkina et al (2019) observed higher GSH synthesis in leaf blades of Triticum aestivum grown at 4°C exposed to Cd than in plants grown at 4°C without Cd exposure. According to these authors, the higher GSH synthesis in the leaf blades of plants exposed to Cd decreased the lipid peroxidation in the tissue, as we also observed in our study (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, in our study the higher GSH concentrations in the winter conditions can be attributed also to higher Cd tissue concentrations observed in this season, since GSH synthesis is strongly Cd‐induced (Seth et al 2012). Also, Repkina et al (2019) observed higher GSH synthesis in leaf blades of Triticum aestivum grown at 4°C exposed to Cd than in plants grown at 4°C without Cd exposure. According to these authors, the higher GSH synthesis in the leaf blades of plants exposed to Cd decreased the lipid peroxidation in the tissue, as we also observed in our study (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The physiological indexes (MDA content, PRO content, POD activity, CAT activity, and SOD activity) of bread wheat seedlings also verified their sensitivity to drought and salt stress. In addition, in TaRS15-3B -silenced bread wheat plants, stress resistance-related genes ( TaP5CS , TaLEA7 , TaDREB1 ) [ 77 , 78 , 79 ] and ROS scavenging system-related genes ( TaPOD , TaSOD1 , and TaCAT3 ) [ 80 , 81 , 82 ] were down-regulated to varying degrees. The results showed that the silencing of the TaRS15-3B gene would lead to the decline of the ability of bread wheat plants to cope with stress and ROS scavenging system, thus further showing the enhanced sensitivity to drought and salt.…”
Section: Discussionmentioning
confidence: 99%
“…The role of wheat in phytoremediation is sparingly studied; however, few studies reported an increase in the expression of the PC synthase (TaPCS1) gene under Cd stress and Pb stress (Repkina et al, 2019;Rahman et al, 2022). The application of Si to the wheat plants under As stress induces the level of PCs and MTs, which further reduces the translocation of As to the shoot by sequestrating it into the roots of wheat (Hossain et al, 2018).…”
Section: Metal-binding Proteins In Wheatmentioning
confidence: 99%